Tujuan Pengendalian Internal Berbasis Nilai Keamanan Sistem Informasi Dalam Organisasi Perusahaan - Sarawani, Ulfa Dwi; Sasniar, Sasniar (Fakultas Ekonomi, Universitas Cenderawasih, 2021)
This study aims to determine the purpose of value-based internal control for information systemsecurity, incorporate organizations both in terms. of the group and individual information systems inthe organization or company. Internal control plays an important role in the overall effectiveness ofinformation system security. A theoretical framework of means-fundamental objectives for internalcontrol in the context of information systems security is presented. Data were collected throughin-depth interviews with 52 IT managers about their values in defining internal control. A total of68 objectives were identified which were organized into 25 groups of seven basic objectives and 18means. These findings provide the basis for further theoretical exposition in the field of securitygovernance. They also assist in defining policy initiatives related to governance. This research wasconducted library research (library research) by collecting data from sharing existing literature,articles obtained from internet searches. The results obtained from this study are: How is thesecurity for physical and non-computer resources, protection from loss or unexpected changes todata and networks.